On New Type of F-Contractive Mapping for Quasipartial b-Metric Spaces and Some Results of Fixed-Point Theorem and Application - A. M. Zidan; Asma Al Rwaily (Journal of Mathematics)
In this paper, we introduce the concept of new type of F-contractive type for quasipartial b-metric spaces and some definitions and lemmas. Also, we will prove a new fixed-point theorem in quasipartial b-metric spaces for F-contractive type mappings. In addition, we give an application which illustrates a situation when Banach’s fixed-point theorem for complete quasipartial b-metric spaces cannot be applied, while the conditions of our theorem are satisfying.